A Contemporary History of Suicide Bombing: A Sociological Approach to 9/11 - Usep Abdul Matin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2008)
I argue in this paper that the 9/11 phenomenon was not individual problem, but a problem of larger social issues. In the introduction of this paper, I clarify the above statement by Peter Berger in light of C. Wright Mills’ idea of the sociological imagination. Having clarified this, I discuss the behavior of the 9/11 hijackers in light of conflict and functionalist-oriented paradigms.